(3GdCMGOjK GdCQHYjf aj EUWfGY GdeYQha Edi GdeSdejf hbVGA MhGFL Gdedghajfs - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi Tehd aVdg hfYeg GdMOjK GdChd Yf CfS QVi Gddg Yfg Cf GdfHi Udi Gddg Ydjg hSde bGd (B: ( (3GdNdb cdge YjGd Gddg aCMH Ndbg Edjg CfaYge dYjGdg (B) s
(3BNQgG (B:s
(3GdMOjK GdCQHYhf Yf GHf YeQ bGd bjd jG QShd Gddg Ci GdfGS CMH Edjc bGd CfaY GdfGS ddfGS bGd aCi GdYed CaVd bGd EONGdc GdSQhQ Ydi GdeDef hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3fSNI ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B30s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP YHO GdeMSf Hf MeO GdYHGO s
Keywords: (3GdMOjK h GdeUWdMs